Palliative embolisation for intrapulmonary shunting in lepidic predominant adenocarcinoma of the lung. (2015) - Tan, Joanne Yue-Ai; Walters, Darren L.; Poon, Karl; Zimmerman, Paul; Aldons, Pat
Abstract: Lepidic predominant adenocarcinoma (LPA) (formerly known as bronchioalveolar carcinoma) has rarely been reported to cause refractory hypoxia with intrapulmonary shunting [1–7]. We describe a case who underwent the palliative strategy of intravascular right lower pulmonary artery embolisation with an 18 mm Amplatzer II vascular plug to reduce intrapulmonary shunting. This is the first report we are aware of using this minimally invasive procedure to treat this condition.